Description of Hanifin-Rajka Criteria and Skin Hydration in Adult Patients with Mild-Moderate Atopic Dermatitis at Tertiary Hospital - Menul Ayu Umborowati; Faradistiani Rakhmawati Jastika; Made Putri Hendaria; Sylvia Anggraeni; Damayanti; Maylita Sari; Cita Rosita Sigit Prakoeswa (Department of Dermatology and Venereology, Faculty of Medicine, Universitas Airlangga, 2024)
Background: Atopic dermatitis (AD) is a chronic inflammatory skin disorder that typically manifests in childhood and has a diverse etiology. In the United States, the prevalence of AD among adults was 4.9%, while in Japan it was 2.1%. The majority of people with AD have dry skin. Hanifin-Rajka criteria were the first to be established and are frequently used as diagnostic standards in research. Purpose: The purpose of this study is to determine the Hanifin-Rajka criteria and skin hydration in adult patients with mild-moderate atopic dermatitis at Dr. Soetomo General Academic Hospital, Surabaya March-May 2022.  Methods: This cross-sectional descriptive study included adult patients with mild to moderate AD according to Hanifin-Rajka aged 18-64 years who visited the Dermatology and Venereology Outpatient Dr. Soetomo General Academic Hospital Surabaya between March and May 2022. Skin hydration was measured using a corneometer on the volar side of the left forearm in the skin area.  Result: Based on the major criteria, all participants had pruritus, typical morphology and distribution, and chronic or chronically recurrent dermatitis. As for the minor criteria, more varied results were obtained, one of which was xerosis, which was experienced by all participants. The skin hydration shows that the mean value for skin hydration was 39.8 ± 12.1. The lowest skin hydration was 21.4 and the highest was 87.4, both found in subjects with mild AD. Conclusion: ..